Fundraising as a source of funding for public university libraries in Kenya - Ngetich, Festus K; Rotich, Daniel C; Otike, Japhet (Mousaion, 2016)
The aim of this study was to examine fundraising as a viable supplementary source of funding for public university libraries in Kenya. Ideally, university libraries require sufficient funding in order to play their role effectively, which is to support teaching, learning and research activities in the university. However, inadequate allocation of funding to public university libraries in Kenya over the years has negatively affected the quality of their services. Therefore, there is an urgent need for these libraries to consider fundraising as a source of funding. The study used a sample of 102 respondents comprising Librarians, Finance Officers (FOs), Heads of Alumni Departments (ADs), Heads of Students Advisory Departments (SADs) and Heads of Fundraising and/or Development Departments (F/DDs) drawn from seven public university libraries in Kenya. The major findings of the study revealed that public university libraries in Kenya carry out fundraising activities as a source of supplementary funding albeit on a minor scale due to negative staff attitude and lack of a proactive approach to strategizing and coordinating creative forms of fundraising. Although these libraries use some motivational strategies to attract and retain donors, they face a number of fundraising challenges. However, the study findings indicated that fundraising can be a viable source of supplementary funding for public university libraries in Kenya if it is well planned and coordinated.
Keywords: academic libraries; funding; fundraising; libraries; public university libraries; research-based universities; university libraries; Kenya